Willful Hermeneutical Ignorance and the "Critical Race Theory" Controversy. Issue 6 (19th January 2023) - Applebaum, Barbara
Abstract: In this article, Barbara Applebaum examines "the inability to disagree claim" as it arises in objections made by those who want to ban "critical race theory" from being taught in schools and universities. Employing insights from the recent scholarship around willful hermeneutical ignorance, she discerns the important role that marginalized conceptual resources play in conditions of just and constructive dialogue. When such resources are misinterpreted and denied uptake, the resulting harm impedes the epistemic agency of marginally situated knowers. Applebaum claims that many high‐profile anti–"critical race theory" arguments put forth by politicians, scholars, and others are a form of willful hermeneutical ignorance, and she concludes by showing how more just communications, in which disagreement is distinguishable from dismissal, can be achieved.